2021
DOI: 10.11591/ijece.v11i3.pp2490-2499
|View full text |Cite
|
Sign up to set email alerts
|

Counteraction to information influence in social networking services by means of fuzzy logic system

Abstract: The article describes a decision support system based on fuzzy inference aimed to automate the procedure of choosing a model of formalizing the interaction between actors in virtual communities of social networking services and synergistic management of such processes. The developed system aims to increase the effectiveness of counteracting threats to information security of the state in social networking services. The mathematical apparatus of the fuzzy set theory and the Mamdani algorithm are the basis for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
(33 reference statements)
1
3
0
Order By: Relevance
“…This result implies that when the habitual perspective increases, one's susceptibility to SECA also increases, in the context of using a social media messaging application. This study is in accordance with research conducted by Albladi and Weir [18] and Molodetska et al [35], which found frequent status updates and a high Human Behavior and Emerging Technologies number of contacts that comprise a habitual perspective can increase the level of susceptibility to SECA. Another study that indirectly supports this finding is by Darwish et al [33], who found that a higher frequency of online shopping also leads to greater susceptibility to phishing attacks.…”
Section: Habitual Perspectivesupporting
confidence: 93%
“…This result implies that when the habitual perspective increases, one's susceptibility to SECA also increases, in the context of using a social media messaging application. This study is in accordance with research conducted by Albladi and Weir [18] and Molodetska et al [35], which found frequent status updates and a high Human Behavior and Emerging Technologies number of contacts that comprise a habitual perspective can increase the level of susceptibility to SECA. Another study that indirectly supports this finding is by Darwish et al [33], who found that a higher frequency of online shopping also leads to greater susceptibility to phishing attacks.…”
Section: Habitual Perspectivesupporting
confidence: 93%
“…This level of engagement can be measured in many ways, i.e., number of friends or connections, posts, groups followed, etc. Users that show high levels of social or virtual network engagement are more exposed to SE attacks [61]. In SE attacks, trust and deception can further be classified into sub-domains, as shown in Table 6.…”
Section: Trust and Deceptionmentioning
confidence: 99%
“…In [9], a fuzzy set decision support system is presented for automating the procedure for selecting a model to formalize interactions between actors in virtual communities and social networks. In this case, a system of fuzzy indicators for evaluating the elements of information impact is used.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The results of the analysis of works related to the identification of methods of manipulation in messages distributed on the Internet [8][9][10][11][12][13][14][15][16][17] indicate that today there is no comprehensive approach to determining the methods of IPI in text messages. The use of indicators proposed in [8][9][10][11][12][13][14][15][16][17] does not imply further automated solution of the content analysis problem.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%